Paradigmatic Analysis of a Metaphorical Expression (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper proposes the existence of a particular type of constructional idiom, that it referred to as ‘paradigmatic pattern’. It is shown that, while it is clearly a metaphorical expression, it does not participate in a systematic conceptual mapping that could explain its central role in framing immigration discourse. It is presented an analysis in terms of the concept of paradigmatic phraseological patterns mentioned above. It is concluded by sketching the outlines of an extension of Metaphorical Pattern Analysis (Stefanowitsch 2006) that captures conceptual mappings not only between source and target domains in the sense of conceptual metaphor theory, but between domains of any kind and that as Paradigmatic Pattern Analysis.